Peran Masyarakat Muslim Perumahan Kedundung Indah Dalam Membentuk Karakter Anak Kota Mojokerto Jawa Timur - Laili Nur Baiti; Hasyim Asy’ari (Journal of Social, Educational and Religious Studies, 2025)
Character formation can be formed through the surrounding community, especially in residential areas. The practice of the Muslim community that is customary in the residential area has an impact on the formation of the character of the children around it. Therefore, the Muslim community in a housing complex has an impact on forming the character of children. This study aims to reveal the strategies and implications of the Muslim community in the Kedundung Indah housing complex in forming the character of children in the city of Mojokerto. This study uses qualitative with a case study approach, the researcher as a direct observer. The data is the activities of the Muslim Community carried out in the Kedung Indah housing complex. The data collection technique uses interviews, observation and documentation. Data analysis uses the Miles and Huberman model. Then, the validity of the data uses Triangulation of sources, time and techniques. The results of this study indicate that the Strategy of the role of the Muslim Community is implemented through the activities of Congregational Prayer, Majelis Taklim, Istighosah, Sholawat banjari and Pesantren Ramadhan. While the implications of the activities that are the Muslim Community that form the character of children in the form of Religious Character, Disciplined Character, Responsible Character, Hard Working Character and Honest Character.